2021
DOI: 10.1002/jbio.202100257
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory responses in α‐ and β‐cells by near‐infrared (810 nm) photobiomodulation

Abstract: Significant efforts have been committed to better understand and regulate insulin secretion as it has direct implications on diabetes. The first phase of biphasic insulin secretion in response to glucose lasts about 10 minutes, followed by a more sustained release persisting several hours. Attenuated insulin release in the first phase is typically associated with abnormal β‐cells. While near‐infrared photobiomodulation (PBM) demonstrates potential for multiple therapeutic applications, photostimulatory effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Crous et al [43] reported an increase in ROS production in adipose-derived mesenchymal stem cells exposed to a low-power infrared (825 nm) laser in continuous-wave emission mode. Liebman et al [44] demonstrated that exposure to a low-power infrared (810 nm) laser elevated the intracellular ROS levels. In addition, Gholami et al [45] reported an increase in ROS levels in periodontal ligament stem cells after exposure to a low-power pulsed infrared (940 nm) laser.…”
Section: Discussionmentioning
confidence: 99%
“…Crous et al [43] reported an increase in ROS production in adipose-derived mesenchymal stem cells exposed to a low-power infrared (825 nm) laser in continuous-wave emission mode. Liebman et al [44] demonstrated that exposure to a low-power infrared (810 nm) laser elevated the intracellular ROS levels. In addition, Gholami et al [45] reported an increase in ROS levels in periodontal ligament stem cells after exposure to a low-power pulsed infrared (940 nm) laser.…”
Section: Discussionmentioning
confidence: 99%
“…Liebman et al. ( 165 ) reported improvement of insulin secretion of beta cells and glucagon of alpha cells associated with a rise of calcium activity. Irani et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological stimulation has been shown to increase calcium activity through drugs such as tolbutamide, which closes the K ATP channels of the β-cells [48,49]. In addition to EFS, noninvasive stimulation can occur through applications such as photobiomodulation (PBM) therapy [7]. Using this pipeline, the direct comparison of changes in calcium dynamics between different stimuli can now readily be explored.…”
Section: Plos Onementioning
confidence: 99%
“…The main function of β-cells is the production and secretion of insulin. The release of this hormone is triggered by an increase in ATP [7] as the blood becomes oversaturated with glucose. As intense research efforts continue to explore this disease, many of the mechanisms behind insulin secretion are yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%